Determinants and measurement of smart growth: evidence from Poland - Rafał Żelazny (Journal of International Studies)
The paper deals with smart growth as a new economic category. The first part presents the theoretical aspects of this concept. The second part shows the results of smart economy development measuring for Poland based on the creative economy index (CEI) in the period of 2005–2014. Polish economy in the years 2005-2014 improved the conditions for smart growth – its CEI increased by 47%. This outcome consists of the results in four intermediate composite indicators, i.e.: inventive economy (IE), political institutions (PI), business regulations (BR) and fiscal institutions (FI). At the time, the largest percentage increase was recorded for the political institutions subindex (263%), followed respectively by the business regulations subindex (189%) and then inventive economy subindex (26%). During the same period fiscal institutions subindex decreased by 30%.